Malignant lymphomas in Korea. - Chi, J. G. (Korean Academy of Medical Sciences, 1987)
A retrospective histological study of 540 malignant lymphomas diagnosed at the Department of Pathology of the Seoul National University from 1976 through 1986 is presented. Malignant lymphoma is the 10th most common malignant tumor in Korea, comprising 3.07% of all malignancy during period of study. Among malignant lymphomas non-Hodgkin's lymphoma accounted for 82% and accordingly the Hodgkin's disease was for 18%. The most common type of non-Hodgkin's lymphoma was diffuse histiocytic lymphoma of Rappaport. Follicular lymphoma was very rare, comprising only 2.3%. T-cell lymphoma accounted for 9.6% of non-Hodgkin's lymphomas, the most frequent type being lymphoblastic lymphoma. Immunoblastic sarcoma and mycosis fungoides were occasionally seen but there was no case of pleomorphic adult T-cell lymphoma. Among Hodgkin's diseases, mixed cellularity type was the most common type, and nodular sclerosis type was relatively rare.